Information and Communication Technologies in Education, Research, and Industrial Applications 18th International Conference, ICTERI 2023, Ivano-Frankivsk, Ukraine, September 18-22, 2023, Proceedings - Antoniou, Grigoris; Ermolayev, Vadim; Kobets, Vitaliy; Liubchenko, Vira.; Mayr, Heinrich C.; Spivakovsky, Aleksander; Yakovyna, Vitaliy; Zholtkevych, Grygoriy (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book constitutes the proceedings of the 18th International Conference, ICTERI 2023, held in Ivano-Frankivsk, Ukraine, during September 18-22, 2023. The 21 full papers included in this volume were carefully reviewed and selected from 90 submissions. The volume focuses on research advances in ICT, business or academic applications of ICT, and design and deployment of ICT infrastructures.
Invited talk -- Main Conference -- PhD Symposium -- Poster Papers. .
Keywords: Education -- Data processing; Artificial intelligence; Software engineering; Application software; Computers and Education; Artificial Intelligence; Software Engineering; Computer and Information Systems Applications